Preferences, monetary policy and household inflation - Geoffrey Dunbar (Bank of Canada, 2024)
Household inflation can be decomposed into three terms that reflect nominal expenditure, real quantities and household preferences, using the money pump proposed by Echenique, Lee and Shum (2011). I quantify the importance of changes in household preferences on household inflation rates using 11 years of scanner data for 11,000 US households. I then analyze the effect of monetary policy on household inflation using the monetary policy shocks from Nakamura and Steinsson (2018). I find that monetary policy news shocks affect household inflation through the expenditure and preferences channels for 12 months from the date of the shocks, and that federal funds rate shocks affect inflation through the same channels at a horizon of 13-24 months. The results suggest that changes in household preferences are an important driver of inflation dynamics at the household level.
Keywords: D12; E52; E58; 330; Inflation and prices; Monetary policy transmission